2017
DOI: 10.1371/journal.pone.0178720
|View full text |Cite
|
Sign up to set email alerts
|

Does time-lapse imaging have favorable results for embryo incubation and selection compared with conventional methods in clinical in vitro fertilization? A meta-analysis and systematic review of randomized controlled trials

Abstract: ObjectiveThe present study aimed to undertake a review of available evidence assessing whether time-lapse imaging (TLI) has favorable outcomes for embryo incubation and selection compared with conventional methods in clinical in vitro fertilization (IVF).MethodsUsing PubMed, EMBASE, Cochrane library and ClinicalTrial.gov up to February 2017 to search for randomized controlled trials (RCTs) comparing TLI versus conventional methods. Both studies randomized women and oocytes were included. For studies randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…However, its clinical effectiveness over conventional morphology is still under discussion. In a recent meta-analysis, Chen et al (2017) showed that clinical TLM may have the potential to improve outcomes but that more evidence was needed, while Pribenszky et al (2017) concluded in another meta-analysis to an improvement of pregnancy rates and lower pregnancy losses when using TLM. The pros and cons were recently debated in a review on the main topics related to TLM (Paulson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its clinical effectiveness over conventional morphology is still under discussion. In a recent meta-analysis, Chen et al (2017) showed that clinical TLM may have the potential to improve outcomes but that more evidence was needed, while Pribenszky et al (2017) concluded in another meta-analysis to an improvement of pregnancy rates and lower pregnancy losses when using TLM. The pros and cons were recently debated in a review on the main topics related to TLM (Paulson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the initial hierarchical model described by Meseguer et al, (2011) was compared to classical morphological selection in three RCTs (Rubio et al, 2014;Semra Kahraman et al, 2012;Siristatidis et al, 2015) whereas Goodman et al, (2016) used their own algorithm. A recent meta-analysis concluded that the use of time-lapse monitoring was associated with a significantly higher ongoing clinical pregnancy rate, significantly lower early pregnancy loss and a significantly increased live birth rate compared with morphological selection (Pribenszky et al, 2017), whereas another review gave conflicting results (Chen et al, 2017). Additionally, a validated predictive model based on multicentric morphokinetic databases analysis has been reported (Petersen et al, 2016), however no universally applicable morphokinetic marker or model to predict embryo implantation has yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is the focus on a surrogate outcome (fertilisation rate) rather than the clinical outcome (live birth) that has presumably influenced clinical decision making; trials of randomised oocytes suggest that a strategy of ICSI in non‐male infertility could reduce the number of cases of total fertilisation failure, but an improvement in live births has not been demonstrated. Similarly, pre‐implantation genetic testing and time‐lapse systems for embryo incubation are becoming routine practice in many clinics, despite a lack of robust evidence of clinical benefit …”
Section: The Gap Between Clinical Practice and Evidencementioning
confidence: 99%
“…Similarly, pre-implantation genetic testing and time-lapse systems for embryo incubation are becoming routine practice in many clinics, despite a lack of robust evidence of clinical benefit. 8,9 Marketing trumps informed patient choice…”
Section: The Gap Between Clinical Practice and Evidencementioning
confidence: 99%
“…Time-lapse technology means that sequential images of embryos are recorded during culture with the use of a digital inverted microscope in order to accurately assess the embryo's development (74). Despite the promising outlook, there are numerous studies reporting that time-lapse technology should not be employed, at least not yet, as part of an IVF laboratory's routine due to the lack of adequate data and evidence supporting its efficiency and its contribution towards improving success rates of implantation rates and clinical pregnancies (75)(76)(77). Nonetheless, employment of time-lapse technology as a novel approach in the laboratory routine promises to revolutionize embryo culture as we know it, enabling continuous access to the embryo's preimplantation developmental journey and eliminating the factor of exposure while recording precious information.…”
Section: Latest Trendsmentioning
confidence: 99%